Recovering Buddhism in modern China - Kiely, Jan, 1965-; Jessup, J. Brooks (New York : Columbia University Press, 2016)
Modern Chinese history told from a Buddhist perspective restores the vibrant, creative role of religion in postimperial China. It shows how urban Buddhist elites jockeyed for cultural dominance in the early Republican era, how Buddhist intellectuals reckoned with science, and how Buddhist media contributed to modern print cultures. It recognises the political importance of sacred Buddhist relics and the complex processes through which Buddhists both participated in and experienced religious suppression under Communist rule. Today, urban and rural communities alike engage with Buddhist practices to renegotiate class, gender, and kinship relations in post-Mao China.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 9, 2016).
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Buddhism -- China; Buddhism; China; PHILOSOPHY -- Buddhist; RELIGION -- Comparative Religion; Electronic books; History